The Effect of Malicious Envy on Schadenfreude When Schadenfreude Is Elicited Through Social Comparisons - Lin, Huiyan; Liang, Jiafeng (Frontiers in Psychology, 2021)
Previous studies have investigated whether envy, particularly malicious envy, increases feelings of schadenfreude, and whether this effect is evident in both gain and loss frames. However, as a social-comparison-based emotion, schadenfreude was not investigated through social comparisons in these previous studies. Thus, the present study aimed to investigate whether malicious envy influences schadenfreude when schadenfreude is elicited in the context of precise and ambiguous social comparisons. To address this issue, participants in the present study were asked to play a monetary game with several other players. In the experimental condition, participants gained less or lost more than the other player; in the control condition, both the participants and the player gained little or lost much. Subsequently, the participants observed that the player encountered a misfortune, i.e., gained less or lost more money than the participant. The results showed that when participants knew the exact amount of monetary gained and lost by themselves and the other player (i.e., precise social comparisons), malicious envy increased feelings of schadenfreude only in the loss frame rather than in the gain frame. More importantly, malicious envy turned out to reduce feelings of schadenfreude in both gain and loss frames, when participants did not know the exact amount (i.e., ambiguous social comparisons). The findings provide novel evidence that malicious envy does not always increase schadenfreude particularly when schadenfreude is elicited through social comparisons.